The factors influence the motivated employees at amber clm resource., jsc company - Phạm, Xuân Nghị (2020)
Amber CLM resource., JSC is an enterprise operating in the field of multi-metal mining, having main factory located in PhaMueng Ward, Bolikhan District, Bolikhamxay Province, Lao People’s Democratic Republic. Because it is a Vietnamese legal entities but implementing a multi-metal ore mining project in Laos, the project has to use a lot of employees from many different countries and labor force also ranges from expert level, senior management, to unskilled labor. Because of the above reasons, managers have to even more promptly grasp the thoughts and aspirations of the staff, thereby having the right solutions to motivate employees’ work motivation. To be able to do this, managers needs to know which factors affect employees’ motivation, while no research or report has been done at this enterprise. Research model is created to study the factors influencing employees’ motivation of at Amber CLM resource., JSC company. The proposed model includes 01 dependent variable as work motivation and 08 independent variables included: (1)Communication; (2)Teamwork; (3)Initiative working; (4)Time management; (5)Self-control; (6)Training; (7)Recognition; (8)Benefit-Income. Based on Chapter I theory and qualitative research results, the scale for 08 independent variables and